Legal Position for the Implementation of Inheritance Distribution - Ridwan Hulalata (Universitas Negeri Gorontalo, 2021)
Abstract : This study aims to determine the legal position of the distribution of inheritance in Sonuo Village, West Bolangitang District, North Bolaang Mongondow Regency. This type of research is normative-empirical, by taking a sociological juridical research approach (Sociological jurisprudence) which is based on a legal provision regarding the norm system, but observing how the reactions and interactions occur when the norm system works in society. Based on this view, empirical legal research using a Sociological Jurisprudence approach is a research. The results of this study indicate that the practice of dividing inheritance used by the people of Sonuo Village is using traditional procedures. Inherited property is for the heirs themselves without discriminating between sons and daughters. There are parents who divide their wealth to the heirs during his lifetime, and there are also later after the heirs die. The people of Sonuo Village, since then, have been more inclined to the Inheritance Sharing scheme which has been passed down from ancestors/customs in the village. Until now, the people of Sonuo Village, which still cannot be called modern society, still adhere to the beliefs or beliefs that have been passed down from their previous parents in determining the distribution of inheritance, which is certainly different from the point of view of Islamic law in determining inheritance.